Public procurement of interregional passenger transports and Swedish transport policy in practice since 1988: Towards new regional patterns? - Martin Eriksson; Thomas Pettersson (European Regional Science Association (ERSA), 2010)
Traditionally, Sweden has not belonged to the Anglo-Saxon market-centred welfare model. However, Sweden is today among the European countries with the highest degree of public outsourcing and procurement of welfare services via competitive markets. The aim of this article is to investigate the development of procurement of inter-regional railway passenger transports and to explore how this affected the allocation of public resources since 1988. Did procurement only increase the efficiency of policy implementation (same or better service for the same or lower price), or did it also indirectly affect the outcome of policy (the relative allocation of public resources between regions and modes of transportation)? The article shows that procurement enabled new regional interest groups to affect the outcome of policy, which in turn changed the allocation of subsidies to railway passenger transports. The results are relevant for the future organization of the transport sector to avoid unwanted side effects from procurement and other new organizational models.'
Keywords: 330